2023
DOI: 10.3390/pathogens12080975
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Drug Resistance of Strong Biofilm-Producing Acinetobacter baumannii Strains Isolated from Infections and Colonization Hospitalized Patients in Southern Poland

Abstract: Acinetobacter baumannii (AB) is a bacterium that causes infections, particularly in immunocompromised patients. Treatment is challenging due to biofilm formation by AB strains, which hinders antibiotic effectiveness and promotes drug resistance. The aim of our study was to analyze the biofilm-producing capacity of AB isolates from various forms of infections in relation to biofilm-related genes and their drug resistance. We tested one hundred isolates for biofilm formation using the crystal violet microplate m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The study Kasperski et al. also highlighted the high prevalence of strong biofilm-forming A. baumannii among XDR isolates, originating from ICU patients [ 54 ]. Some authors associate high-levels of biofilm-formation to the presence or absence of specific factors; such are the studies of Azizi et al.…”
Section: Discussionmentioning
confidence: 99%
“…The study Kasperski et al. also highlighted the high prevalence of strong biofilm-forming A. baumannii among XDR isolates, originating from ICU patients [ 54 ]. Some authors associate high-levels of biofilm-formation to the presence or absence of specific factors; such are the studies of Azizi et al.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown the presence of ompA (detection from 81 to 100%), csuE (detection from 80 to 100%), and bap (detection from 43 to 91.4%) in clinical A. baumannii strains producing strong biofilms [232,[244][245][246][247][248]. In a recent study, Kasperski et al [249] reported that 72% of strong biofilm producer A. baumannii strains harbored four genes associated with biofilm formation (bap, bfmS, csuE, and ompA), showing their implication in bacterial adhesion on surfaces.…”
Section: Acinetobacter Baumanniimentioning
confidence: 99%
“…Biofilm formation by isolates was analyzed and categorized based on the absorbance of attached cells by crystal violet staining. The biofilm formation ability was then divided into 4 categories, i.e., none (OD≤ODc), weak (ODc<OD≤2xODc), moderate (2xODc<OD ≤4xODc), and strong (4xODc<OD) (Pompilio et al 2020, Kasperski et al 2023. A comparison test was performed using an independent t-test.…”
Section: The Research Process Began With the Identification Of Staphy...mentioning
confidence: 99%

Biofilm Formation in Staphylococcus aureus and Coagulase-Negative Staphylococcus

Marta Setiabudy,
Dewa Ayu Putri Sri Masyeni,
Anak Agung Gede Indraningrat
et al. 2023
FMI